2018
DOI: 10.1152/advan.00088.2018
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a virtual neurophysiology laboratory as a new pedagogical tool for medical undergraduate students in China

Abstract: This study compared the effect of a virtual laboratory, a living tissue laboratory, and a blended laboratory on student learning about the generation and conduction of neural action potentials and perceptions about life science. Sixty-three second-year medical students were randomly assigned to one of three groups (living tissue laboratory, virtual laboratory, and blended group). The students conducted the practical activity, and then they were given a postlaboratory quiz and an attitude survey. The blended gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…Furthermore, technical laboratory staff assist the educators in setting up the laboratory experiments, calibrating, and checking equipment and making solutions. Before the pandemic, some educators had replaced traditional hands-on (on-campus) physiology laboratories with nontraditional, virtual alternatives (7,8). The terminology for nontraditional laboratories in the research literature is confusing, with inconsistent use of terms such as simulation and virtual, remote, and distance laboratories (9).…”
Section: Context Of Physiology Education: What Are Laboratories?mentioning
confidence: 99%
“…Furthermore, technical laboratory staff assist the educators in setting up the laboratory experiments, calibrating, and checking equipment and making solutions. Before the pandemic, some educators had replaced traditional hands-on (on-campus) physiology laboratories with nontraditional, virtual alternatives (7,8). The terminology for nontraditional laboratories in the research literature is confusing, with inconsistent use of terms such as simulation and virtual, remote, and distance laboratories (9).…”
Section: Context Of Physiology Education: What Are Laboratories?mentioning
confidence: 99%
“…The VLs can open new perspectives for higher education sustainability (Salmerón-Manzano & Manzano-Agugliaro, 2018). The VL can be used as a new pedagogical tool for undergraduate students as per the study carried out in China and it is suggested that the blended laboratory is the best laboratory (Wang et al, 2018). The VLs can improve students’ understanding and also enrich their knowledge as per the outcome of the study carried out in Taiwan (Shyr, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Six out of the eleven studies investigated whether the virtual physiology laboratories were effective for motivational learning. Five out of the six studies (83.3%) supported this, with three of these studies comparing blended models with in-person models (24,25,37), one study comparing virtual with in-person laboratories (41), and one study comparing both virtual and blended models with an in-person model (16). One study compared virtual models with in-person models and showed that the virtual models were not effective for students' motivational learning (7).…”
Section: Are Virtual Laboratories Effective For Motivational Learning?mentioning
confidence: 90%
“…The majority of the studies that investigated conceptual learning showed that the virtual physiology laboratories were effective for students' conceptual learning. This was tested using quantitative analysis of test scores, with the "pretest-posttest" design (13,24,38,39) or the "posttestonly" design (7,16,25,(40)(41)(42). The pretest-posttest design allows the measurement of baseline values to be used as references to show the significance of changes before and after the intervention (43), whereas the posttest-only design measures only the performance of the participants after the intervention without baseline values, which can induce biases and errors (44).…”
Section: Conceptual Learningmentioning
confidence: 99%